Previously incarcerated individuals with psychotic symptoms are more likely to report a history of solitary confinement. (August 2020) - Ryan, Arthur T.; DeVylder, Jordan
Highlights: Individuals with psychotic disorders are disproportionatley represented in the U.S. prison system. We collected survey data from a community sample of previously incarcerated individuals. Individuals with psychotic symptoms were more likely to have been placed in solitary confinement. Abstract: We examined whether previously incarcerated individuals with self-reported psychotic symptoms were more likely to endorse a history of solitary confinement. A community-based sample of 176 previously incarcerated individuals residing in Baltimore or New York City were surveyed on prison experiences and mental health symptoms. Logistic regression found that previously incarcerated individuals who endorsed a schizophrenia diagnosis or past 12-month psychotic symptoms were significantly more likely to report a history of solitary confinement while incarcerated. This finding is consistent with other research suggesting that individuals with psychotic illness are disproportionately subjected to solitary confinement while incarcerated, which has important socio-legal implications.